2021
DOI: 10.3389/fspas.2021.654879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metals on (Star)Dust Chemistry: A Laboratory Astrophysics Approach

Abstract: Laboratory experiments are essential in exploring the mechanisms involved in stardust formation. One key question is how a metal is incorporated into dust for an environment rich in elements involved in stardust formation (C, H, O, Si). To address experimentally this question we have used a radiofrequency cold plasma reactor in which cyclic organosilicon dust formation is observed. Metallic (silver) atoms were injected in the plasma during the dust nucleation phase to study their incorporation in the dust. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The plateau in the AgI line intensity suggests an additional source of release of Ag atoms into the plasma compared to the silver sputtering from the target since the electron temperature is decreasing at that time (Figure 3). This additional source could be either the AgNPs or the dissociation of Ag n clusters and complexes of Ag with hydrocarbons whose presence has been demonstrated in our earlier study (Bérard et al, 2021). The coinciding plateau in the intensity of the AgI line and the bump in the intensity of the ArI line can be associated with the moment when the AgNPs attach to the organosilicon NPs to form the core-satellite assemblies (raspberry-like NPs).…”
Section: Transition In the Plasma Behavior During Simultaneous Plasma...mentioning
confidence: 65%
See 1 more Smart Citation
“…The plateau in the AgI line intensity suggests an additional source of release of Ag atoms into the plasma compared to the silver sputtering from the target since the electron temperature is decreasing at that time (Figure 3). This additional source could be either the AgNPs or the dissociation of Ag n clusters and complexes of Ag with hydrocarbons whose presence has been demonstrated in our earlier study (Bérard et al, 2021). The coinciding plateau in the intensity of the AgI line and the bump in the intensity of the ArI line can be associated with the moment when the AgNPs attach to the organosilicon NPs to form the core-satellite assemblies (raspberry-like NPs).…”
Section: Transition In the Plasma Behavior During Simultaneous Plasma...mentioning
confidence: 65%
“…Although these studies are relatively recent and the achievements are not yet numerous, dust formation in reactive plasmas based on large chemical precursors has already been identified as promising for the development of thin nanocomposite films for microelectronic devices, sensor applications, healthcare applications, among others. In addition, it has recently been shown that the formation of dust nanoparticles in HMDSO-based plasmas appears to be of some interest for the study of stardust formation in laboratory experiments (Bérard et al, 2019;Bérard et al, 2021), as HMDSO contains key elements involved in stardust: carbon, oxygen, and silicon (Henning, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the investigation of the emergence and growth of dust particles in a 13,56 MHz radio-frequency (RF) discharge plasma, sustained in a mixture of argon and hexamthyldisiloxane (Ar-HMDSO) with HMDSO being the molecular precursor, is being carried out [24 -26]. Based on the formation of particles in a dusty plasma, the mechanisms of cosmic dust formation and the synthesis of its analogues in laboratory conditions are being investigated [27].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mass spectrometry analysis revealed that various carbonaceous samples contain a dominant peak at m / z = 202.078 corresponding to a polycyclic aromatic hydrocarbon (PAH) of formula C 16 H 10 . These samples include soot particles generated in flames, diesel fuels and particulate matter, cosmic dust analogues, , and carbonaceous chondrite meteorites. Shukla and Koshi showed that in combustion reactions, different chemical pathways lead to the preferential formation of pyrene or fluoranthene. Each isomer could then lead to different species by subsequent growth.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been applied to soot samples. , Recent work in our group has demonstrated the very high sensitivity (attomole level) of the two-step LDI-MS in following molecular families of PAHs, carbon clusters, hydrogenated carbon clusters, and fullerenes. We have applied this technique to the analysis of laboratory analogues of stardust ,, and of meteorite samples. ,,, An originality of our setup is to be equipped with an ion trap so that ions can be activated by collisions or by absorption of photons and their dissociation features used to obtain information on the structure of the ions.…”
Section: Introductionmentioning
confidence: 99%